Assessment of the Ferroptosis Regulators: Glutathione Peroxidase 4, Acyl-Coenzyme A Synthetase Long-Chain Family Member 4, and Transferrin Receptor 1 in Patient-Derived Endometriosis Tissue - Mielke Cabello, Lidia A. (2024)
Ferroptosis, a novel iron-dependent form of non-apoptotic cell death, plays a pivotal role in various diseases. In the realm of endometriosis, ferroptosis is an emerging and relatively unexplored topic, characterized by inherent ambiguity regarding its physiological significance. This case-control study is a comprehensive immunohistochemical assessment of the expression and tissue distribution of established ferroptosis markers: GPX4, ACSL4, and TfR1 in endometriosis patients. Our study revealed a significant downregulation of GPX4 in stromal cells of endometriosis patients (M = 60.8% ± 42.3 versus 90.5% ± 17.2 in the control group, t (56) = -2.94, p = 0.005). This finding aligned with slightly higher iron levels detected in the blood of endometriosis patients, using hemoglobin as an indirect predictor (Hb 12.9 ± 1.1 g/dL versus 12.2 ± 1.9 g/dL in the control group; t (56) = -1.621, one-sided p = 0.055). Interestingly, there was no concurrent upregulation of TfR1, responsible for iron uptake into cells. The strongest correlations were found between GPX4 and ACSL4 as ferroptosis inhibitor and inductor, respectively. Our empirical findings provide support for the involvement of ferroptosis in the context of endometriosis. However, variances in expression patterns within stromal and epithelial cellular subsets call for further in-depth investigation.